THE INFLUENCE OF THE TENDENCY FROM LEARNING STYLE OF GRADE III TOWARD MATH FINAL LEARING - Isnawati, Isnawati; Widyasari, Widyasari; Supriatna, Irfan (DIDAKTIKA TAUHIDI: JURNAL PENDIDIKAN GURU SEKOLAH DASAR, 2016)
Every person or student have different style in learningproses and it is possible that they have different result. Tendencion of learning style and low result of math in third grade can see from the tendencion of learning process they have. It is can be seen by visual, auditorial, and kinestetic. The purpose of this research is it know the differences of result of the math, viewed by the tendencion of learning style in visual, auditorial, and kinestetic. The method of this research is descriptive quantitative with comparative research methodology. The result is a value one way anova as F â table 3,18 >F â count 0.051 on significant level (sig) > Î±: 0,05 which mean Ho accepted and Ha unaccepted, end decision is that no differences about result level viwed by the tendencion of learning style in visual, auditorial, and kinestetic.